PENGARUH CITRA MEREK DAN KUALITAS PELAYAAN TERHADAP KEPUASAAN KONSUMEN PADA JASA PENGIRIMAN BARANG J&T (Studi pengguna jasa pengiriman J&t Express di kecamatan purwasari kabupaten karawang) - Rizaldi Cholif Arahman; Dadan Ahmad Fadili (Jurnal Mirai Management, 2021)
In modern times, the delivery service sector has experienced a very fast increase compared to the previous period. The world is entering a digital era called the Industrial Revolution 4.0 era, which is an era that emphasizes the digital economy. "Everything is digital" is the right word for this decade. The increase in the frequency of delivery of goods can also be based on the increase in online purchases in today's modern era. J&T Express is a company engaged in the delivery of goods in Indonesia. J&T Express, which has been established for the last 5 years, serves delivery to all inland cities and outside the city and abroad. The purpose of this study is to determine and analyze the correlation, partial effect and simultaneous influence between erectile image and service quality on J&T Express consumer satisfaction in Purwasari. The research method used is quantitative with descriptive and verification approaches with a sample of 287 samples and using techniques Sampling Non Probability Sampling. The analysis used is path analysis. The results of this study are that there is a correlation between the variables of brand image and service quality 0.756 which has a strong positive and significant correlation. There is a partial influence between Brand Image on consumer satisfaction, Service Quality on consumer satisfaction. There is a simultaneous positive and significant influence between brand image, service quality and consumer satisfaction. Keywords: Brand Image_, Service Quality_, Consumer Satisfaction.